DEVELOPMENT OF A REALISTIC MATHEMATICS EDUCATION MODULE BASED ON COASTAL CULTURE TO IMPROVE NUMERATION LITERACY - Susanto, Hendra; Thahura, Farahdiba (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2026)
Despite high cognitive potential from fish consumption, coastal students face boring traditional modules; thus, a culture-based RME-AI module was developed to enhance numeracy skills. This study aims to analyze the level of validity, practicality, and effectiveness of the Realistic Mathematics Education (RME) learning module based on coastal culture with the Gemini application and how the module can improve the numeracy literacy skills of fifth grade students. The RME module development leverages students' environmental reality to facilitate mathematical learning, effectively bridging pedagogical gaps to achieve superior educational goals through contextual experiences and meaningful conceptual mastery. So that with this module it can help students in improving numeracy literacy skills. The RME-based module is said to be suitable for use if it meets three criteria: valid, practical, and effective. Based on the results of the research analysis, 1) the module was declared very valid after being revised with a percentage of 89.00%, 2) the module was declared practical with an average student response questionnaire result of 84.00% in the field test. Furthermore, 3) the normalized gain test was used to determine how effective the RME learning module was in improving students' numeracy literacy skills. The gain test results showed a value of 0.35 which indicates moderate. This means that the RME learning module based on coastal culture is effective in improving students' numeracy literacy skills. The implications suggest integrating local wisdom bridges abstract-reality gaps, while Gemini AI offers scalable, culturally-responsive models that significantly enhance student engagement and long-term retention of numeracy skills.